The Impact of Technological Innovation and Digital Arts Development on Chinese Guangdong Higher Vocational Education: A Theoretical Model and Empirical Analysis - Wang, Wu; Wan, Qiang; Cui, Jun; Liu, Lisha (Transactions on Economics, Business and Management Research, 2024)
This paper investigates the impact of digital technological innovation and the development of digital arts on Guangdong higher vocational education in China, Guangdong. Using a comprehensive theoretical framework, the study examines the roles of mediators and moderators in this relationship. Besides, this study uses a) Innovation Diffusion Theory, c) Social Cognitive Theory and b) Technology Acceptance Model (TAM) theories for research and analysis. So that, the research employs a mixed-methods approach, integrating qualitative and quantitative analyses, and tests six hypotheses through structural equation modeling (SEM). The findings provide insights into the dynamic interplay between digital technology and education, highlighting implications for policy and practice in the Chinese Guangdong context. Utilizing a structural equation modeling (SEM) approach, the study examines the mediating and moderating roles of teacher proficiency, institutional support, student attitudes, and education resource availability.  Moreover, the findings reveal that technological innovation significantly enhances educational quality, while digital media arts development fosters student engagement and creativity. Meanwhile, Chinese Guangdong’s Teacher proficiency and student attitudes act as crucial mediators, and institutional support and resource availability function as important moderators. Consequently, this research fills a gap in understanding how technology and arts integration influences vocational education, offering valuable insights for policy and practice in the Chinese Guangdong higher educational context.